53.5k views
2 votes
Ben solved an equation as shown below, Equation 2 (-3×+1)=9×-8. what did he do wrong. step1. -6×+2=9×- 8. step2. -6×+9×=-8+2. step3. 3x=-6. step4. x=-2

User Abbr
by
5.2k points

2 Answers

3 votes

failed to evaluate 9 × - 8

2( - 3x + 1) = 9 × - 8

- 6x + 2 = - 72 ( subtract 2 from both sides )

- 6x = - 74 ( divide both sides by - 6 )

x =
(-74)/(-6) =
(37)/(3)



User Shengy
by
5.8k points
2 votes
He just switched sides of the variables and numbers. Instead if adding the opposite.
User Srh
by
5.9k points